Changing the firing threshold for normal optic nerve axons by the application of infra-red laser light - Lavinia J. Austerschmidt; Nadine I. Schottler; Alyssa M. Miller; Mark D. Baker (Scientific Reports, 2021)
Abstract Normal optic nerve axons exhibit a temperature dependence, previously explained by a membrane potential hyperpolarization on warming. We now report that near infra-red laser light, delivered via a fibre optic light guide, also affects axonal membrane potential and threshold, at least partly through a photo-thermal effect. Application of light to optic nerve, at the recording site, gave rise to a local membrane potential hyperpolarization over a period of about a minute, and increased the size of the depolarizing after potential. Application near the site of electrical stimulation reversibly raised current-threshold, and the change in threshold recorded over minutes of irradiation was significantly increased by the application of the I h blocker, ZD7288 (50 µM), indicating I h limits the hyperpolarizing effect of light. Light application also had fast effects on nerve behaviour, increasing threshold without appreciable delay (within seconds), probably by a mechanism independent of kinetically fast K+ channels and Na+ channel inactivation, and hypothesized to be caused by reversible changes in myelin function.